EVALUASI KOMPETENSI MAHASISWA PRAKTIK PENGALAMAN LAPANGAN KEPENDIDIKAN (PPLK) PROGRAM STUDI PENDIDIKAN GEOGRAFI UNP - Silvi - Yuliani; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
ABSTRACT This study aims to evaluate the competence of students in the field experience of education (PPLK) in the UNP geography education study program. This research is a descriptive research with a quantitative approach. The population of this study were all geography tutors in PPLK july 2019 semester at pariaman city high school. The technique of sampling is total sampling. The data collection technique is a questionnaire with data collection tools, namely a questionnaire given to respondents. The result of this study can be concluded that (1) in this study it can be seen that the evaluation of the competence of students in the field experience of education (PPLK) of the UNP geography education study program seen from the pedagogical competence is in the goog category with a score of 65,08. (2) in personality competence, it can be seen that the evaluation of the competence of students in the field experience of education (PPLK) of the UNP geography education study program is in the good category with a score of 37,25. (3) in social competence, it can be seen that the competency evaluation of students in the field experience of education (PPLK) of the UNP geography education study program is in the good category with a score of 48,25. (4) on professional competence, it can be seen that the evaluation of the competence of students iin the field experience practice (PPLK) of the UNP geography education study program is in the quite good category with a score of 26,75.